PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. POS INDONESIA (Persero) SIBOLGA - Puja Lestari Melayu; Rosmita Ambarita; Rahmadiah Hanum (CV. Aksara Global Akademia, 2023)
For this study aims to determine the influence of organizational culture and organizational commitment to employee performance at PT. Pos Indonesia (Persero) Sibolga by withdrawing the hypothesis that there is an influence of organizational culture and organizational commitment on employee performance at PT. Pos Indonesia (Persero) Sibolga . The results showed that there was a positive relationship between organizational culture and employee performance of 0.617, so that when interpreted on a value scale it can be categorized as sufficient correlation, thus the variable organizational commitment to employee performance is 0.684 which is categorized as sufficient correlation at PT. Pos Indonesia (Persero) Sibolga . The regression equation obtained is Y = 21.783 - 0.099 X1 + 0.512X2. The t test shows that the proposed hypothesis is accepted, where t count is -0.371 <2.03011, which means that the hypothesis that there is an influence of organizational culture on employee performance is rejected, while the hypothesis that there is an effect of organizational commitment on employee performance is proven significant, where t is smaller from t table (3.714 > 2.04841). While the coefficient of determination is known that organizational culture and organizational commitment only play a role of 24.2% on employee performance at PT. Pos Indonesia (Persero) Sibolga and the remaining 75.8% is influenced by other factors not included in the model. Hypothesis Testing There is an influence of organizational culture and organizational commitment simultaneously on purchasing decisions that are accepted as true, where Fcount is greater than Ftable, namely 7.015 > 3.35. /Anova (hypothesis test)